PENGARUH LAMA PERKECAMBAHAN MILLET (Panicum milliaceum) TERHADAP KARAKTERISTIK FLAKES - Dewi, I Gusti Agung Ayu Sintia Padma; Ekawati, I Gusti Ayu; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2018)
The purpose of this research was to know the effect of germination time of millet (Panicum milliaceum) on the characteristics of flakes and to know the right germination time of millet on the characteristics of flakes. The experimental design used was completely randomized design with the germination time of millet treatment, namely 24 hours (T1), 48 hours (T2), 72 hours (T3), 96 hours (T4), and 120 hours (T5). The treatment was repeated 3 repetitions then obtained 15 units of the experiment, the data obtained from the result were analyzed by variance and if the treatment had an effect on the variable then continued with Duncan test. The results showed that the germination of millet had significant effect to water content, ash content, protein content, fat content, crude fiber content, tannin content, taste level (hedonic test), and overall acceptance of flakes. 120 hours germination time of millet had the best characteristics with water content 1,36%, ash content 2,65%, protein content 9,93%, fat content 7,86%, carbohydrate content 78,20%, crude fiber content 5,93, tannin content 0,31%, color liked, flavor liked, texture crispy and liked, taste liked  and overall acceptance liked.